Gypsum lakes, sandflats and soils revealed from the Triassic Red Peak Formation of the Chugwater Group, north‐central Wyoming - Maya Yamei Bradford; Kathleen C. Benison (The Depositional Record, 2024)
Abstract Bedded gypsum is relatively common in bedded evaporites associated with red bed siliciclastics of Permo‐Triassic Pangea. However, little attention has been paid to the textures of ancient gypsum, which can be used to refine interpretations of depositional environment and diagenetic history. This project describes the textures of bedded gypsum from an outcrop of the Triassic Red Peak Formation (Chugwater Group) near Greybull, Wyoming. Fieldwork, petrography and X‐ray diffraction reveal three distinct lithologies of bedded gypsum: bottom‐growth gypsum, laminated gypsum and clastic gypsum. Bottom‐growth gypsum precipitated at the bottom of shallow saline surface water bodies. Laminated gypsum probably formed in shallow saline lakes and mudflats. Clastic gypsum units are composed of aeolian‐reworked bottom‐growth gypsum crystals deposited in sandflats. Red siliciclastic mudstones are characterised by their massive nature and abundant blocky peds. Detailed study of this outcrop of the Red Peak Formation shows that it formed in shallow saline lakes and associated mudflats, sandflats and desert soils.